The role of the psychedelic experience in psilocybin treatment for treatment-resistant depression - Goodwin, Guy M; Aaronson, Scott T; Alvarez, Oscar; Carhart-Harris, Robin; Chai-Rees, Jamie; Croal, Megan; DeBattista, Charles; Dunlop, Boadie W; Feifel, David; Hellerstein, David J; Husain, Muhammad I; Kelly, John R; et al. (Journal of affective disorders, 2025)
OBJECTIVE: To determine the relationships between psilocybin dose, psychedelic experiences, and therapeutic outcome in treatment-resistant depression. METHODS: For treatment-resistant depression, 233 participants received a single dose of 25, 10, or 1 mg of COMP360 psilocybin (a proprietary, pharmaceutical-grade synthesized psilocybin formulation, developed by the sponsor, Compass Pathfinder Ltd.) with psychological support. The resulting psychedelic experience (Five-Dimensional Altered States of Consciousness questionnaire [5D-ASC] and Emotional Breakthrough Inventory [EBI]) were measured. These proximal variables and outcome 3 weeks post-administration (change in Montgomery-Åsberg Depression Rating Scale [MADRS]) were explored using correlation analysis. RESULTS: The mean intensity of psychedelic effects was dose-related, but distributions of scores for different doses overlapped considerably. Depression response correlated with select aspects of the psychedelic experience overall and for individual doses. At the 25 mg dose, 5D-ASC dimensions Oceanic Boundlessness (Pearson correlation coefficient r = -0.508) and Visual Restructuralization (r = -0.516), and EBI (r = -0·637) were the variables with the strongest correlation to the Week 3 change from Baseline in MADRS score. LIMITATIONS: The existence of correlation does not establish causation and exploratory findings require further replication, preferably in larger independent samples. CONCLUSIONS: The intensity of psychedelic experience overlaps widely across doses and mitigates the risk of unblinding to dose. Correlations between psychedelic experience and outcome suggest specificity in psilocybin's mechanism of action. Quality and intensity of psychedelic experience may be a measure of pharmacodynamic effect and reveal an effective dose response phenomenon for single oral doses.
Keywords: výsledek terapie; halucinogeny; Male; Depressive Disorder, Treatment-Resistant; Depressive Disorder, Major; vztah mezi dávkou a účinkem léčiva; Adult; psilocybin; dospělí; mužské pohlaví; Hallucinogens; dvojitá slepá metoda; deprese nereagující na léčbu; Treatment Outcome; lidé; ženské pohlaví; Humans; Psilocybin; depresivní porucha unipolární; Double-Blind Method; psychiatrické posuzovací škály; Female; Dose-Response Relationship, Drug; lidé středního věku; Psychiatric Status Rating Scales; Middle Aged